The Impact of Flap Creation Methods for Sub-Bowman’s Keratomileusis (SBK) on the Central Thickness of Bowman’s Layer - Xu, Zhe; Shen, Meixiao; Hu, Liang; Zhuang, Xiran; Peng, Mei; Hu, Di; Liu, Jing; Wang, Jianhua; Qu, Jia; Lu, Fan (PloS one, 2015)
To determine the impact of flap creation methods for sub-Bowman's keratomileusis (SBK) on central Bowman's layer thickness. SBK flaps were made by Moria microkeratome for 20 subjects and by femtosecond (FEMTO) laser for 21 subjects. Corneal sublayer thicknesses were measured by ultra-high resolution optical coherence tomography before SBK and at 1 day, 1 week, 2 weeks, and 1 month afterwards. Each subject was imaged twice on each visit. Thicknesses of central epithelium, Bowman's layer, flap, and total cornea were calculated using a custom-made automated image processing algorithm. The repeatability of sublayer thickness measurements was tested by the intraclass correlation coefficient (ICC) and by the coefficient of repeatability (CoR) at 1 week post-SBK. ICCs of the Moria and FEMTO groups were ≥ 0.959 and ≥ 0.961 respectively for all sublayer measurements. The segmentation CoRs were less than 6.78% and 5.63% respectively. For both groups, microdistortions were present in the epithelium and Bowman's layer after SKB. The flap thickness of the Moria group was 9.8 μm (95% confidence interval: 4.8 - 14.8 μm) thinner than the FEMTO group one day after SBK (independent samples t-test, P < 0.05). Bowman's layer became thicker by 1.6 ± 1.1 μm and 1.7 ± 1.6 μm one day post-SBK for the Moria and FEMTO groups (repeated ANOVA, P < 0.05) and then remained stable. Corneal and sublayer thickness were similar between the two groups. Central Bowman's layer thickness increased 1 day post-SBK. Flap creation by Moria microkeratome and femtosecond laser did not have significantly different impacts on Bowman's layer thickness following SBK. Chinese Clinical Trial Registry (ChiCTR) NO: ChiCTR-OCH-14004525.